Analysis of Internal Control System of Cash Receipts and Expenditures of Muhammadiyah Development Islamic Vocational School Tana Toraja - Masnawaty Sangkala (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to determine the suitability of internal control in the cash receipt and cash disbursement system of SMK Pesantren Pembangunan Muhammadiyah Tana Toraja with the components of internal control according to experts, one of which is according to Widjajanto, the components tested in this study are the organizational structure that clearly separates functional responsibilities, the authority system and recording procedures, healthy work practices, employees whose quality is in accordance with their responsibilities. The variables of this study are: the internal control system of cash receipts and disbursements as a single variable using qualitative methods. The population of this study is the internal control system of cash receipts and disbursements of SMK Pesantren Pembangunan Muhammadiyah Tana Toraja, while the sample is the internal control system of cash receipts and disbursements of SMK Pesantren Pembangunan Muhammadiyah Tana Toraja for the last year of the 2020 period which was taken using data collection and data analysis techniques. Data collection was carried out by interviews (using Internal Control Questionnaires), observation and documentation. Data analysis was carried out using qualitative descriptive (ICQ and flowchart). The results of this study indicate that the internal control system for cash receipts and disbursements at SMK Pesantren Pembangunan Muhammadiyah Tana Toraja is not fully in accordance with the application of internal control elements contained in the theory that is guided by the Standard Operating Procedure (SOP) for Financial Management at SMK Pesantren Pembangunan Muhammadiyah Tana Toraja.